Identification of lactic acid bacteria and quality parameter of Tempeh obtained from red kidney beans (Phaseolus vulgaris) and cowpeas (Vigna unguiculata) - Gergonius Fallo; Yuni Sine (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
.